16(3x-6)=12(-12+4x)

Simple and best practice solution for 16(3x-6)=12(-12+4x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16(3x-6)=12(-12+4x) equation:



16(3x-6)=12(-12+4x)
We move all terms to the left:
16(3x-6)-(12(-12+4x))=0
We add all the numbers together, and all the variables
16(3x-6)-(12(4x-12))=0
We multiply parentheses
48x-(12(4x-12))-96=0
We calculate terms in parentheses: -(12(4x-12)), so:
12(4x-12)
We multiply parentheses
48x-144
Back to the equation:
-(48x-144)
We get rid of parentheses
48x-48x+144-96=0
We add all the numbers together, and all the variables
48!=0
There is no solution for this equation

See similar equations:

| V2-5v+6=0 | | -3(w-8)=-3 | | -3x+32-7x=-2(5x+10 | | 3y-5=2(4y+2) | | 6k^2+3=0 | | (5-3i)(9+6i)=0 | | 4x^2-15+12=-2x+2 | | 6=2(z-3) | | -1/2x+5/3=-7x-3/4 | | 5/6w=3 | | 11q+14q+-6=-15 | | -6(-44x+15)=-41(30-x) | | 0=-4.9t^2+42t+2.5 | | 1-6v=25 | | 2-5i=0 | | -11q+14q+6=-15 | | (6-z)(3z+1)=0 | | -69x-13=87+39x | | 16a-18a+-14a=-16 | | -123/40=9/10p+3/40 | | 3xx-5=2xx | | 7k-3k+3=31 | | -25=x-13 | | 100=1/2x | | -9=u/6-3 | | 16a−18a+-14a=-16 | | 9x-3(2x+4)=2(x-12) | | 7a–6=-1–11a | | 4(3x-9)=6(-6+2x) | | S35=x/16 | | 4x^2-16x+256=0 | | q=2.5P |

Equations solver categories